2012
DOI: 10.1111/j.1476-5381.2011.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

2′‐Methoxy‐6‐methylflavone: a novel anxiolytic and sedative with subtype selective activating and modulating actions at GABAA receptors

Abstract: BACKGROUND AND PURPOSEFlavonoids are known to have anxiolytic and sedative effects mediated via actions on ionotropic GABA receptors. We sought to investigate this further. EXPERIMENTAL APPROACHWe evaluated the effects of 2′-methoxy-6-methylflavone (2′MeO6MF) on native GABAA receptors in new-born rat hippocampal neurons and determined specificity from 18 human recombinant GABAA receptor subtypes expressed in Xenopus oocytes. We used ligand binding, two-electrode voltage clamp and patch clamp studies together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 57 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…Recently, its pharmacokinetic profile in animals was also reported (Khan et al, 2014b). Viscosine is structurally related to the CNS-active flavonoids, 2′-MeO6MF (Karim et al, 2012) and 3-OH2′ MeO6MF (Karim et al, 2011). Unlike 2′-MeO6MF and 3-OH2′ MeO6MF, viscosine has hydroxy groups on C5 and C7 and methoxy groups on C3 and C6 (Fig.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, its pharmacokinetic profile in animals was also reported (Khan et al, 2014b). Viscosine is structurally related to the CNS-active flavonoids, 2′-MeO6MF (Karim et al, 2012) and 3-OH2′ MeO6MF (Karim et al, 2011). Unlike 2′-MeO6MF and 3-OH2′ MeO6MF, viscosine has hydroxy groups on C5 and C7 and methoxy groups on C3 and C6 (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…More recently flavonoids such as amentoflavone (Hanrahan et al, 2003), 6-methylflavone (Hall et al, 2004), 6-methylflavanone (Hall et al, 2005), 6-hydroxyflavone (Ren et al, 2010), 2′-methoxy-6-methylflavone (2′MeO6MF) (Karim et al, 2012) and 3-hydroxy-2′methoxy-6-methylflavone (3-OH-2′MeO6MF) (Karim et al, 2011) have been shown to modulate GABA A receptors and many exert anxiolytic effects in mouse models of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…2′-Methoxy-6-methyllavone has demonstrated anxiolytic efects in mice at 1 and 10 mg/kg using the elevated plus maze model of anxiety [54]. It was also found to act as a positive modulator at α2β1γ2L and all α1-containing GABA A receptor subtypes, demonstrated via recombinant GABA A receptors expressed in Xenopus oocytes [54].…”
Section: Synthetic Lavonoidsmentioning
confidence: 99%
“…It was also found to act as a positive modulator at α2β1γ2L and all α1-containing GABA A receptor subtypes, demonstrated via recombinant GABA A receptors expressed in Xenopus oocytes [54]. By contrast, it directly activated α2β2/3γ2L receptors without potentiating GABA [54].…”
Section: Synthetic Lavonoidsmentioning
confidence: 99%
See 1 more Smart Citation